Pengaruh Variasi Rotation Time Terhadap CTDI (CT Dose Index) dan DLP (Dose Leght Product) Pada Pemeriksaan CT Kepala Non Kontras - Gabriel Barreto De Carvalho Belo; Kadek Yuda Astina; Made Adhi Mahendrayana (Lembaga Pengembangan Kinerja Dosen, 2024)
Background. Non-contrast head CT scans utilizing X-rays are considered the gold standard in emergency units for patients with clinical head injuries. Rotation time is a parameter that influences the radiation dose received by patients. This study aims to evaluate the impact of rotation time on patient radiation doses, emphasizing the ALARA principle. The research findings can assist in optimizing CT scan settings to reduce radiation doses without compromising image quality.. Methods: This quantitative research employs an experimental approach to investigate the influence of rotation time variations on CTDI (CT dose index) and DLP (dose leght product) in non-contrast head CT scans. Results: Calculation of CTDI and DLP values to assess the impact of rotation time variations, using two variations, 1 s and 1.5 s, yielded the following results: CTDI and DLP for 1 s were 20.30 mGy and 239.54 mGycm, respectively, while CTDI and DLP for 1.5 s were 20.43 mGy and 249.26 mGycm. Conclusion: Rotation time variations affect CTDI and DLP values in non-contrast head CT scans, although both values tend to remain stabel. A rotation time of 1 s is considered optimal for CTDI and DLP in non-contrast head CT scans at the Radiology Department of Sunset Vet Kuta Animal Hospital.